Analisis Kinerja Mesin Ring Frame Spinning 5 Menggunakan Metode Overall Equipment Effectiveness (OEE) dan Six Big Losses pada PT Indorama Synthetics Tbk. - Fauziah, Silva; Wibowo, Priyo Ari; Ulum, Rikzan Bachrul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the performance of the Ring Frame Spinning 5 machine at PT. Indorama Synthetics Tbk using the Overall Equipment Effectiveness (OEE) method and Six Big Losses approach. The research was conducted quantitatively using data from September 2024 to February 2025. The analysis showed that the average OEE value was 83.476%, which is below the World Class OEE standard of 85%. The highest losses were identified in Idling & Minor Stoppage (20.72%) and Reduced Speed Losses (24.56%). The root causes of these losses were analyzed using fishbone diagrams and the 5W + 1H method, focusing on factors such as manpower, machines, methods, materials, and the production environment. Recommended improvements include operator training, SOP implementation, scheduled machine component replacement, and environmental control in the production area.